A crystal-growth boundary-fusion strategy to prepare high-quality MAPbI3 films for excellent Vis-NIR photodetectors. (October 2019) - Wang, Tao; Lian, Gang; Huang, Liping; Zhu, Fei; Cui, Deliang; Wang, Qilong; Meng, Qingbo; Jiang, Haihui; Zhou, GuangJun; Wong, Ching-Ping
Abstract: Rendering high-quality perovskite films is integral for excellent performance of optoelectronic devices and highly challenging as well. Here, we establish a two-round pressure-assisted solvent-engineering (TPS) strategy to achieve remarkable enhancement in grain size ( 400 μm 2 ), crystallinity, orientation and, especially, boundary fusion. Crystal growth and boundary welding of MAPbI3 grains are mainly attributed to pressure-enhanced ion diffusion and defect elimination, which facilitates lateral enlargement of grains and formation of ultra-smooth film. Dramatic diminution of trap density determines long carrier lifetime and improved lateral charge transport, as demonstrated by the superior performance of MAPbI3 -based photodetectors, e.g. ultrahigh on/off ratio ( 10 6 ), good stability, fast response, high responsivity and high detectivity (1.3 × 10 14 Jones). When upconversion nanoparticles are uniformly assembled on the high-quality MAPbI3 films, interestingly, the hybrid device exhibits dominantly elevated photoelectric capability in near infrared range (NIR, 980 nm) with long-term stability in ambient air. The results and method pave a novel way for ongoing fabrication of efficient and stable optoelectronic devices based on high-quality perovskite films. Graphical abstract: Two-round pressure-assisted solvent-engineering strategy is designed to achieve remarkable enhancement in grain size ( 400 μm 2 ), crystallinity, orientation and, especially, boundary fusion. Crystal growth and boundary welding of MAPbI3 grains, ascribed to pressure-enhanced ion diffusion and defect elimination, vastly reduce trap density, suppress charge recombination, and thus improve the charge transport. The corresponding photodetectors exhibit superior photoelectric performance at Vis-NIR regions, e.g. ultrahigh on/off ratio, fast response and high detectivity.Image 1 Highlights: A pressure-enhanced ion diffusion strategy improves the grain size, orientation and boundary fusion of perovskite films. The crystal-grown and boundary-fused MAPbI3 grains vastly reduce trap density and thus improve the charge transport. The MAPbI3 films present superior photoelectric performance as Vis-NIR photodetectors.